Characterizing of Air Pollution in Tehran: Comparison of Two Air Quality Indices - Saeed Motesaddi; Yalda Hashempour; Parviz Nowrouz (Salehan Institute of Higher Education, 2017)
Multi-pollutant air pollution dramatically occurs in wide range of regions across Tehran. Air quality index (AQI) is applied worldwide to inform the public about levels of air pollution and related to health risks. Assessing air pollution, and transferring information about its possible adverse health effects, may encourage population and policy makers to reduce activities that increase pollution levels. In this study the Air quality index (AQI), Aggregate Air quality index (AAQI), and a relative index of variability (VR) were obtained for the data in order to better investigate air pollution conditions for the whole areas of a city of Tehran, aim at warning the people of short-term health impact. The proposed index of variability does add precious information to the aggregate AQI, as it can demonstrate whether the value assumed by the AQI is influenced by one or more pollutants. The two indices are together used on simulated data and consider different possible scenarios. In addition, Applications to real air pollution data are reported. Before applying the two indices, the effects of different standardizations on data are evaluated from a theoretical point of view.